Potential use of grape stems and pomaces from Touriga Nacional and Marselan cultivars as source of polyphenols and oligosaccharides - Mangione, Roberta (2022)
Mestrado em Engenharia de Viticultura e Enologia (Double degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto